Diggers - Pratchett, Terry (New York : Delacorte Press, 1990)
A group of small creatures called nomes, whose families have lived for generations hidden in a department store, are forced to flee to a country quarry, where they struggle against harsh weather, destructive humans, and dissension among themselves.
Kirkus Review.
School Library Journal.
5.0
5.0
5-8.
5-8
Keywords: Science fiction; Fantastic fiction